Malaysian Tākāful Agents' Ethical Professional Behavior: A Systematic Literature Review - Arini Abdullah, Nor; Akram Hassan , Shahir (Journal of King Abdulaziz University: Islamic Economics, 2023)
This paper examines the ethical behaviour of Malaysian tākāful agents through extensive exploration of several studies on ethical practices in the tākāful industry. The ethical behaviour of the tākāful agent contributes to inevitable consequences in the agent's efforts to attract participants to join tākāful schemes. These positive or negative consequences affect both participants and tākāful businesses. Despite the abundance of research on tākāful agents, research that applies the systematic literature review (SLR) method on the ethical behaviour of the tākāfultākāful agent is rarely available; therefore, this gap needs to be filled. The purpose of this study is to examine the ethical behaviour at work of the tākāful agent. Journal articles related to the ethical behaviour of tākāful agents were analyzed by applying the systematic literature review (SLR) method, which was guided by PRISMA (Preferred Reporting Items for Systematic Review). Five themes were identified based on the results of the SLR, namely Islamic Relationship Marketing (IRM), sales ethics, tākāful participants' trust, agent role, and agent performance. The results of this study indicate that the ethical behaviour of tākāful agents can be further identified by involving the tākāful company and tākāful participants. The results suggest that tākāful agents should educate themselves by improving their tākāful product knowledge and communication skills, as Muslim customers considering tākāful policies are strongly influenced by how tākāful agents promote tākāful policies or products. It is recommended that future research highlight the bidirectional relationship between tākāful agents' ethical behaviour toward tākāful businesses and participants. To achieve this, tākāful companies or the Malaysia tākāful Association (MTA) should play an important role by conducting in-depth interview sessions or obtaining feedback from tākāful agents.